Odpowiedź :
Odpowiedź:
[tex](\frac{1}{x^2}+\frac{1}{x}-1)(2x^2-2x^3)=\frac{1}{x^2}(2x^2-2x^3)+\frac{1}{x}(2x^2-2x^3)-(2x^2-2x^3)=\\\\=\frac{1}{\not x^2}\cdot \not x^2(2-2x)+\frac{1}{\not x}\cdot \not x(2x-2x^2)-2x^2+2x^3=2-2x+(2x-2x^2)-2x^2+2x^3=\\\\=2-2x+2x-2x^2-2x^2+2x^3=2-4x^2+2x^3=2x^3-4x^2+2[/tex]
Odpowiedź:
=1/x2 × (2x2-2x3) + 1/x3 × (2x2-2x3) - 1 × (2x2-2x3) = 1/x2 × x2 × (2-2x) + 1/x3 × x2 × (2-2x) - (2x2-2x3) = (2-2x) + 1/x × (2-2x) - 2x2 - 2x3 = 2-2x + 2-2x/x - 2x2 + 2x3 = 2x-2x2+2-2x-2x3+2x4/x = 2x4-2x3-2x2+2/x